Biokinematic structure of techniques wrestlers during pre-basic training - Sinіgovets S.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The theoretical aspects of freestyle wrestlers. Experimentally investigated the structural elements of techniques during pre-basic training. The study involved 28 young fighters. Held video computer analysis techniques. Identified biomechanical characteristics defined kinematic structure of the temporal and spatial-temporal characteristics of the basic techniques. Shown variability of the individual phases of the basic techniques. Structural dynamics of the resulting velocities of the individual body bioelement fighters showed characteristic changes depending on the mode and direction of the motor action. Found that the predominant contribution to the biokinematic structure of technical actions were resulting velocities torso of young fighters.